A CONTRIBUIÇÃO DO EGRESSO DO CURSO DE ADMINISTRAÇÃO DA UNIVERSIDADE ESTADUAL DE FEIRA DE SANTANA (UEFS) AO DESENVOLVIMENTO DO MUNICIPIO DE FEIRA DE SANTANA - ROCHA, Saulo José dos Santos (2014)
This research aims to discuss how a university can develop competencies, knowledge, skills and attitudes related to human resources, qualifying the undergraduate degree alumni for the social and productive life in the Region. In order to do so, first it discusses the theoretical background of the debate on higher education organizations, with the characterization of the organization concept, considering elements such as: ambiguity of goals, vulnerability to the environment, fragmented professional body, the ability to transform students into professionals as product of their relationship with society, by showing the role of higher education institutions in the development of the regions where they operate, and also in the association between development, region and state university. The work reflects on higher education and university, explaining that the matrix that supports the higher education system is formed by the historical, political and social condition, transforming the higher formal education in an instrument, which must answer to the structuring and restructuring of the region that sustains it. It presents a brief historical evolution of higher education in Brazil, since its beginning, then going through transformations that were reflective of decisions made during changes in the political stance of the country, and reaching the most recent governments. It was then performed a historical review of higher education in the context of the state of Bahia, whose implementation within the state was done in an integrated way with the development of Bahia regions, as well as with educational policy at all levels. The study of higher education in the region, and more specifically, the knowledge of the entire structure of the object of study – the state university of Feira de Santana (Universidade Estadual de Feira de Santana) – UEFS – as well as knowledge about the undergraduate Management degree, since its general history to its institutional structure, made possible to identify that, through the curriculum and the proposed operations, the alumni are being prepared to work in all areas of organizations in general, specially due to the development of competencies, knowledge, skills and attitudes. The research results, according to the final synthesis tables, allow the conclusion that there occurred significant absorption of the fundamental theoretical framework in the academic experience of the UEFS undergraduate Management degree alumni, indicating that these people can graduate with the proper citizenship exercise abilities fully developed and professional abilities well refined and improved.